1972
DOI: 10.1128/jb.111.3.821-824.1972
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Spheroplasts Formed by Cell Wall-Degrading Enzymes from Oerskovia sp

Abstract: Oerskovia sp. produces inducible extracellular enzymes which degrade the walls of various yeasts. Yeast spheroplasts are formed from both log- and stationary-phase cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The strongly lytic culture fluid of an Oerskovia sp. (25) probably contains this type of glucanase. It has now been established that B. circulans WL-12 also produces a lytic-type ,-(1 -_ 3)-glucanase (F. M. Rombouts and H. J. Phaff, unpublished results), which is currently under investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The strongly lytic culture fluid of an Oerskovia sp. (25) probably contains this type of glucanase. It has now been established that B. circulans WL-12 also produces a lytic-type ,-(1 -_ 3)-glucanase (F. M. Rombouts and H. J. Phaff, unpublished results), which is currently under investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Not understood at present is how the lytic j3-(1 --3)-glucanases have access to the wall glucans. The action of these enzymes is not prevented by the outer mannan layer of the wall since they are capable of eliciting protoplast formation from intact yeast cells (23,25,50). Further information is required about the action and properties of the lytic ,B-(1 _ 3)-glucanase.…”
Section: Discussionmentioning
confidence: 99%
“…Since a commercial preparation of chitinase also contained potent /8(1-)3)-glucanase activity (31), it was considered advisable to prepare and characterize a(1-*+3)-glucanase, f(1-3)glucanase, and chitinase. Although other microbial sources of a(1-3)-glucanases (9,11,13) and f8(1-)3)-glucanase (25,35) were known, the presence of an inducer was required to obtain appreciable yields, whereas C. resinae was a constitutive producer of these two activities when the carbon source for growth was mannitol. a-and 18-glucanases were separated (34), and the problem of concurrent chitinase secretion was minimized by mass adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…The protease, Pronase CB (Calbiochem), was incubated with cell wall samples for varying times at 370C in a 0.05 M tris(hydroxymethyl)aminomethanehydrochloride buffer, pH 7.5, containing, per milliliter: CaCl2, 555 ,ug; cycloheximide, 50 ug; and chloramphenicol, 25 .g. The amino acid so liberated was estimated with ninhydrin.…”
Section: Methodsmentioning
confidence: 99%
“…In a preliminary note (10) we reported that an Oerskovia species isolated from soil produces inducible extracellular enzymes that rapidly degrade the walls of various yeasts. Enzyme action on viable cells lyses them or forms spheroplasts depending on osmotic conditions.…”
mentioning
confidence: 99%